PENGEMBANGAN BUKU AJAR KIMIA BAHAN PANGAN TERINTEGRASI ETNOSAINS SEBAGAI SUMBER BELAJAR MAHASISWA CALON GURU (Jurnal Inovasi Pendidikan Kimia, 2021)
In carrying out chemistry learning, lecturers need tools to facilitate the learning process. The most frequently used tool is the textbook. But often textbooks are not as desired. Therefore, lecturers need to compile their own textbooks to match what they want. This research and development aim to produce ethnoscience integrated food macronutrient chemistry textbooks as a source of learning for prospective teacher students and test their feasibility. The textbook development model used is the 4-D (Define-Design-Develop-Disseminate) model according to with modifications. The due diligence is conducted by material experts, learning experts and media experts. The data obtained in the form of quantitative data. The comments, responses and suggestions given are used to revise and improve the textbooks that were developed. Based on the average score given by experts and the readability test by prospective users, it shows that the textbooks developed are very suitable to be used as learning resources for prospective teacher students in food chemistry lectures.